Multicountry cross‐sectional study found that functional gastrointestinal disorders such as colic and functional dyschezia were common in South American infants. (4th January 2018) - Chogle, Ashish; Velasco‐Benitez, Carlos A.; Chanis, Ricardo; Mejia, Milton; Saps, Miguel
Abstract: Aim: Our aim was to perform a population‐based study using Rome III criteria to describe the prevalence of functional gastrointestinal disorders (FGIDs) in infants in three countries in South America. Methods: We conducted a multicountry, cross‐sectional study to investigate the epidemiology of functional gastrointestinal disorders in children aged 0–12 months of age, using the Rome III criteria, in Colombia, Panama and Nicaragua. These patients presented for well‐child visits in primary care clinics in the three countries between May 2015 and October 2016. A Spanish version of the Questionnaire on Paediatric Gastrointestinal Symptoms for Infants and Toddlers was used for the data collection. Results: We included questionnaires completed by 351 parents, and they reported at least one FGID in 141 (40%) infants. The majority were male (56%), with a median age of seven months. Colic and functional dyschezia were the most commonly diagnosed disorders in the whole cohort, at 23% and 15%, respectively. The risk of developing FGIDs was not affected by the marital status of the mother, number of siblings, birth order and history of diarrhoea. Conclusion: Functional gastrointestinal disorders were common in infants from the South American countries of Colombia, Panama and Nicaragua, particularly colic and functional dyschezia.